Contributions to the knowledge of Ceroys (Miroceroys) Piza, 1936 (Phasmatodea: Heteronemiidae): two new mossy stick insects from the Atlantic Forest of Brazil - Crispino, Edgar B.; Ghirotto, Victor M.; Engelking, Phillip W. [UNESP] (Magnolia Press, 2022)
Several lineages of stick insects (Phasmatodea) are poorly studied, especially in the Neotropics. Recently, Brazilian stick insects have been subject of significant research and, among them, the Heteronemiidae, although several genera remain to be explored. Pygirhynchini is an Heteronemiidae lineage currently containing four genera, of which three occur in Brazil: Ceroys, Canuleius and Pygirhynchus. The former is subdivided in Ceroys (Ceroys) and Ceroys (Miroceroys) based on ornamentation variations absence or presence of a spine on the scapus. We describe two new species, Ceroys (Miroceroys) cancelloae sp. nov. and Ceroys (Miroceroys) indicattii sp. nov. based on both sexes and eggs. The new species inhabit submontane, ombrophilous Atlantic Forest in Southeast Brazil and can be differentiated from other Ceroys (Miroceroys) by conspicuous features of external morphology of adults and eggs. We also briefly describe and illustrate nymphal stages of C. cancelloae sp. nov. and present notes on the biology of both species, and a distribution map for the genus, increasing the scarce knowledge of the natural history of phasmids in Brazil.
Keywords: Natural history; Phasmida; Pygirhynchini; Serra da Mantiqueira; Walking stick